1994
DOI: 10.1128/iai.62.3.1026-1031.1994
|View full text |Cite
|
Sign up to set email alerts
|

Immunization against Porphyromonas gingivalis inhibits progression of experimental periodontitis in nonhuman primates

Abstract: Periodontitis is a common infectious disease in which the attachment tissues of the teeth and their alveolar bone housing are destroyed, resulting in tooth loss. The gram-negative anaerobic microorganism Porphyromonas gingivalis has been closely linked to severe forms of the disease. We show for the first time that immunization of the primate Macaca fascicularis with killed P. gingivalis in Syntex Adjuvant Formulation-M inhibits progression of periodontal tissue destruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
88
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 39 publications
6
88
0
1
Order By: Relevance
“…The specific immune response may play an important role in the control of the microbial insult to the host, either by affecting the pattern of colonization by periodontal organisms or by neutralizing products released from the biofilm. Higher titres of antibodies were reported against putative periodontal pathogens in patients with periodontitis compared with clinically healthy controls [ 10-141. Immunization with whole cells or purified components of P. gingivalis reduced levels of the bacterium in experimental animal models and resulted in less bone loss compared with sham-immunized controls [15,16], although in a separate study increased inflammation was observed following immunization…”
Section: Introductionmentioning
confidence: 99%
“…The specific immune response may play an important role in the control of the microbial insult to the host, either by affecting the pattern of colonization by periodontal organisms or by neutralizing products released from the biofilm. Higher titres of antibodies were reported against putative periodontal pathogens in patients with periodontitis compared with clinically healthy controls [ 10-141. Immunization with whole cells or purified components of P. gingivalis reduced levels of the bacterium in experimental animal models and resulted in less bone loss compared with sham-immunized controls [15,16], although in a separate study increased inflammation was observed following immunization…”
Section: Introductionmentioning
confidence: 99%
“…The primate model has provided a bridge for understanding the interaction of the subgingival microbiota with the inflammatory/immune response to selected members of this microbiota to protect against disease progression or to exacerbate the inflammatory process, leading to the progression of disease. [33][34][35][36][37][38][39][40] We and others have shown that characteristics of the inflammatory response and systemic humoral immune responses that accompany ligature-induced periodontitis in various non-human primate species [35][36][37][38][39][41][42][43] parallel those observed in human periodontitis. 6,8,44,45 The baboon has been identified as a useful nonhuman primate model for periodontal disease investigations.…”
mentioning
confidence: 99%
“…Many studies have examined the effect of immunization to P. gingivalis on experimental periodontitis, but the results have been inconsistent. For example, Persson et al (1994) showed that vaccination with P. gingivalis provided protection against experimentally induced periodontitis in the monkey model. In contrast, Ebersole et al (1991) could not demonstrate any protection against experimental periodontitis, using P. gingivalis vaccine in the same model.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the development of a vaccine to prevent periodontal disease by immunization with antigens from Porphyromonas gingivalis have produced variable and conflicting results (Page 2000). Several studies using both mice and primates have demonstrated that immunization with P. gingivalis results in protection against experimentally induced periodontal destruction (Okuda et al 1988, Persson et al 1994, Genco et al 1998, Gonzalez et al 2003, while other animal studies have been unable to demonstrate protection (Ebersole et al 1991, Moritz et al 1998). In humans, numerous studies have demonstrated that patients with periodontitis mount a humoral immune response to plaque bacteria during the course of their disease (Tew et al 1985, Mooney et al 1997, and antibody titres to P. gingivalis have been shown to be inversely related to disease severity (Okuda et al 1988, Mooney et al 1997).…”
mentioning
confidence: 99%